Biological Membranes: Structure, Function, and Their Roles in Disease Pathophysiology - Maitry H. Rathod; Hardini P. Chauhan; Vaibhavi J. Panchal; Hetvi H. Patel; Bisojeet R. Khandai (International Journal of Membranes, 2026)
Biological membranes are important structures that control cellular work, signal transmission, transport, and communication. Dysfunction of membranes has been considered in the development of many diseases, such as cancer, neurodegenerative diseases, and infections, with the distortion of lipid composition, protein activity, and cellular connections involved in the pathogenesis of the disease. The damage on membrane can be caused by oxidative stress, genetic mutation, and environmental influence to disrupt cellular homeostasis. Some therapeutic methods, including drug delivery systems, gene therapy, and membrane stabilization therapies, have the potential to repair membrane integrity and the outcomes of disease. The future studies are aimed at understanding the mechanisms of membrane dynamics, and special attention will be paid to personalized medicine as well as membrane-targeted therapies. The development of membrane biophysics, imaging methods, and gene editing technologies will make our current capacity to create targeted remedies more advanced. Learning about membrane changes at the molecular level will open new vistas for treating diseases and improving patient treatment.
Keywords: Biological membranes; Cancer; Gene therapy; drug delivery; membrane dysfunction; membrane stabilization; neurodegenerative diseases